Uji Aktivitas Antikanker Ekstrak Tanaman Rumput Bambu (Lophatherum Gracile B.) Metode Ultrasonik Terhadap Sel Kanker Payudara T47D - A'yun, Qurrotul; Romaidha, Iqlila; Makani, Mawaqit; ., Sarinah (Jurnal Borneo Cendekia, 2025)
Bamboo grass (Lophatherum gracile B.) is a type of weed that can be utilized as a medicinal plant. Almost all parts of this plant contain secondary metabolites with potential as herbal medicine. This study was conducted to evaluate the breast cancer (T47D) anticancer activity of bamboo grass using an ultrasonic extraction method. The solvents used in this study were 80% ethanol, n-hexane, and chloroform. All extract samples were tested for their breast cancer (T47D) anticancer activity using the MTT assay. The IC50 values of the 80% ethanol, n-hexane, and chloroform extracts were 218.081; 292.412; and 395.144 ?g/mL, respectively. The TLC separation of tannin compounds from the 80% ethanol extract was identified using FTIR. The identification results showed key absorption peaks of tannin compounds, including O-H alcohol, C-O secondary alcohol, aliphatic C-H, C=C alkene, and ortho-substituted aromatic ring, with corresponding wavenumbers of 3455; 1094; 2963; 2929; 1650; and 780 cm?¹.